2007
DOI: 10.1016/j.cognition.2006.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Affective evaluations of objects are influenced by observed gaze direction and emotional expression☆

Abstract: Gaze direction signals another person's focus of interest. Facial expressions convey information about their mental state. Appropriate responses to these signals should reflect their combined influence, yet current evidence suggests that gaze-cueing effects for objects near an observed face are not modulated by its emotional expression. Here, we extend the investigation of perceived gaze direction and emotional expression by considering their combined influence on affective judgments. While traditional respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
219
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(249 citation statements)
references
References 27 publications
25
219
1
4
Order By: Relevance
“…These studies all involved evaluative measures of stimuli previously associated with human faces whose eye gaze orientation toward stimuli varied. Two of these studies found better liking of objects previously associated with an eye gaze directed at them (Bayliss, Paul, Cannon & Tipper, 2006), an effect that vanished when eyes were replaced by arrows as orienting stimuli (Bayliss et al, 2006) or when the faces looked disgusted (Bayliss, Frischen, Fenske & Tipper, 2007). However, these studies relied on explicit evaluative ratings of the objects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These studies all involved evaluative measures of stimuli previously associated with human faces whose eye gaze orientation toward stimuli varied. Two of these studies found better liking of objects previously associated with an eye gaze directed at them (Bayliss, Paul, Cannon & Tipper, 2006), an effect that vanished when eyes were replaced by arrows as orienting stimuli (Bayliss et al, 2006) or when the faces looked disgusted (Bayliss, Frischen, Fenske & Tipper, 2007). However, these studies relied on explicit evaluative ratings of the objects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Because gaze and facial expressions are processed reflexively [8,21] and integratively [22,23], we performed a third experiment to determine whether facial affect could enhance cued influences on perception.…”
Section: Experiments 2: Observed Eye Gaze (A) Methods (I) Participantsmentioning
confidence: 99%
“…For example, the emotional expression of the person being watched is often taken into account when using normal gaze as a predictive cue (Bayliss, Frischen, Fenske, & Tipper, 2007) or when determining mutual gaze (Lobmaier, Tiddeman, & Perret, 2008). Although this information is absent when using artificial gaze, this method does provide an opportunity to look at more complex gaze sequences rather than simple directional processes.…”
Section: The Communicative Role Of Eye Movementsmentioning
confidence: 99%